Kebijakan Cina Melakukan Boikot Terhadap Ritel Fesyen Multinasional H&M Terkait Isu Perbudakan Kapas di Xinjiang - Novi Ratna Cahyani (Journal of Business and Economics Research (JBE), 2022)
Multinational fashion retailer H&M expressed concern over alleged forced labor carried out by China against ethnic Uighurs in the Xinjiang region. The Chinese government has repeatedly denied the allegations, but China's anger at H&M intensified after other countries sentenced China over the issue. Then the boycott policy was shown to H&M, which has contributed to the Chinese economy with its investment in more than 500 stores across China and as one of the major consumers of Chinese garment companies. This article aims to answer the question, "why is China boycotting H&M on the issue of cotton slavery in Xinjiang?" using the framework of economic coercion analysis. The research method used is qualitative through the analysis and interpretation of secondary data. The results showed that China carried out the boycott policy against H&M to punish H&M, harm H&M, and force H&M to change its policy after H&M harmed China's national interests. The conclusion is that China's coercive policy through a boycott of H&M has proven effective in forcing H&M to submit to China.